Corrigendum: Integrative potential of Central European metropolises with a special focus on the Visegrad countries - Šauer, Martin; Pařil, Vilém; Viturka, Milan (Technological and Economic Development of Economy, 2019)
Martin Šauer, Vilém Pařil, Milan Viturka, authors of the article “Integrative potential of Central European metropolises with a special focus on the Visegrad countries”, published in Technological and Economic Development of Economy, 25(2), 219-238, https://doi.org/10.3846/tede.2019.7555 inform that order of names and surnames appeared reversed and would like to make the following correction in the authorship as follows: Martin Šauer, Vilém Pařil, Milan Viturka. The authors regret the error.